Multidrug-Resistant Helicobacter pylori Strains: A Five-Year Surveillance Study and Its Genome Characteristics - Asif Sukri; Alfizah Hanafiah; Hamidah Yusoff; Nur Atiqah Shamsul Nizam; Zarith Nameyrra; Zhiqin Wong; Raja Affendi Raja Ali (MDPI AG, 2022)
Background: The emergence of multidrug-resistant Helicobacter pylori has undermined eradication strategies to prevent the development of gastric cancer. This study was conducted to estimate the prevalence of secondary antibiotic resistance of H. pylori in urban multicultural areas in Malaysia. Methods: From January 2017 to December 2021, gastric biopsies from 218 patients with a history of H. pylori eradication failure were sent to our laboratory for antibiotic susceptibility testing. A minimal inhibitory concentration was determined for six antibiotics, namely metronidazole, clarithromycin, levofloxacin, amoxicillin, tetracycline, and rifampicin using the E-test method. Two multidrug-resistant H. pylori strains identified in this study were subjected to whole genome sequencing. Results: Eradication failure was observed to be significantly higher in the Malaysian Chinese patients than in the Malaysian Indian and Malay patients. H. pylori were successfully isolated from 51 patients (23.4%). Overall, the antibiotic resistance rates of H. pylori to metronidazole, clarithromycin, levofloxacin, and amoxicillin were 82.4% (42/51), 72.5% (37/51), 52.9% (27/51), and 3.9% (2/51), respectively. Resistance to tetracycline and rifampicin were not observed during the study period. Resistance to more than one antibiotic was observed in 82.4% (42/51) of the isolates, of which 42.2% (19/42) were resistant to three antibiotic classes. Resistance to both clarithromycin and metronidazole were most frequently observed in isolates with dual resistance (56.5%; 13/23). Codon substitutions in penicillin-binding protein 1A (V346L, V374L, G595_V596InsG, Y604H, and N608S) were detected in amoxicillin-resistance H. pylori strains. Herein, we report amoxicillin resistance in H. pylori isolated from Malaysian patients, and its resistance mechanism, for the first time. Conclusion: Our results show the increase trend in secondary multidrug resistance in H. pylori isolates, which warrants continuous surveillance.